Distribution of FoxP3+regulatory T-cells in rat’s pancreatic lymph nodes under streptozotocin-induced diabetes and metformin administration - Putilin, D. A.; Kamyshnyi, A. M.; Путілін, Денис Анатолійович; Камишний, Олександр Михайлович; Путилин, Д. А.; Камышный, А. М. (Zaporozhye state medical university, 2015)
Type 1 diabetes mellitus is a T-cell mediated autoimmune disease characterized by the destruction of β-cells of the pancreas. Numerous studies have demonstrated the key role of FoxP3+ regulatory T-cells in the development of type 1 diabetes. The aim of our study:1) to determine the expression patterns of transcription factor FoxP3 in the pancreatic lymph node cells in animal model of diabetes mellitus and 2) to assay an effect of metformin on these processes. Methods and results.The study was conducted on 60 male Wistar rats with streptozotocin-induced modeling diabetes with various duration of the diabetes. Within development of type 1 diabetes mellitus the number of Treg pancreatic lymph nodes has been reduced. Conclusion.These fi ndings demonstrate the ability of metformin to increase the number of Treg. Цукровий діабет 1 типу є Т-клітинно-опосередкованим автоімунним захворюванням, що характеризується руйнуванням β-клітин підшлункової залози. Численні дослідження показали ключову роль FoxP3+ регуляторних Т-клітин у розвитку цукрового діабету 1 типу. З метою визначення особливостей експресії транскрипційного фактора FoxP3 у клітинах панкреатичних лімфатичних вузлів при експериментальному цукровому діабеті та після введень метформіну здійснили дослідження на 60 самцях щурів лінії Вістар, у яких моделювали стрептозотоцин-індукований цукровий діабет із різною тривалістю патологічного процесу, а також після введень метформіну. Визначено, що при розвитку цукрового діабету 1 типу кількість Treg у панкреатичних лімфатичних вузлах знижується, а метформін демонструє здатність збільшувати щільність їхньої популяції. Сахарный диабет 1 типа – T-клеточно-опосредованное аутоиммунное заболевание, характеризующееся разрушением β-клеток поджелудочной железы. Многочисленные исследования показали ключевую роль FoxP3+ регуляторных Т-клеток в развитии сахарного диабета 1 типа. С целью определить особенности экспрессии транскрипционного фактора Foxp3 в клетках панкреатических лимфатических узлов при экспериментальном сахарном диабете и после введений метформина провели исследования на 60 самцах крыс линии Вистар, у которых моделировали стрептозотоцин-индуцированный сахарный диабет с разной продолжительностью патологического процесса, а также после введения метформина. Установлено, что при развитии сахарного диабета 1 типа количество Treg в панкреатических лимфатических узлах снижается, а метформин демонстрирует способность увеличивать плотность их популяции.
Розподіл FoxP3+ регуляторних Т-клітин у панкреатичних лімфатичних вузлах у щурів при стрептозотоцин-індукованому діабеті та при корекції метформіном
Распределение FoxP3+ регуляторных Т-клеток в панкреатических лимфатических узлах у крыс при стрептозотоцин-индуцированном диабете и при коррекции метформином
Keywords: Diabetes mellitus; FoxP3; Metformin; Treg; цукровий діабет; FoxP3; метформін; Treg; сахарный диабет; FoxP3; метформин; Treg